PENGARUH TERAPI BERMAIN CLAY TERHADAP KECEMASAN PADA ANAK USIA PRA SEKOLAH (3-6 TAHUN) YANG MENJALANI HOSPITALISASI DI RUMAH SAKIT BENGKULU - Fusfitasari, Yenni; Eliyanti, Yeni (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
ABSTRACT Problems : Anxiety is the most common feeling experienced by pediatric patients who are undergoing hospitalization. The Aim Of The Research : Knowing the effect of playing clay therapy on anxiety in pre-school aged children (3-6 years) undergoing hospitalization at Harapan and Do'a Hospital Bengkulu City. The Results : The results showed that the average value of anxiety in pre-school age children (3-6 years) who underwent hospitalization before playing clay therapy with an average value of anxiety was 11.75. The results showed that the average value of anxiety in pre-school age children (3-6 years) who underwent hospitalization after playing clay therapy with an average value of anxiety was 8.60. The results of statistical tests obtained p value = 0.000, meaning <0.05 (α) so it can be concluded that there is an effect of playing clay therapy on anxiety in pre-school age children (3-6 years) undergoing hospitalization at Bengkulu Hospital. Conclusions : The results of the study concluded that there was a decrease in the average value of anxiety in pre-school age children (3-6 years) who underwent hospitalization before and after playing clay therapy and by looking at the statistical value it was found that there was an effect of playing clay therapy on anxiety in pre-school age children. (3-6 years) who underwent hospitalization at Bengkulu Hospital.